STRES KERJA MENGGANGGU KUALITAS KEHIDUPAN KERJA KARYAWAN DI PT. UNITED TRACTORS Tbk JAKARTA - Lisa Sarinah (FEBI UIN Sunan Gunung Djati Bandung, 2023)
High quality of work life is essential for an organization to continuously attract and retain its employees. So the objective of this research was to find out information about the influence of organizational climate, and job stress on the quality of work life. The primary data for this survey research were collected by using questionnaires that were distributed to 100 employees of United Tractors Ltd in Jakarta. The data were analyzed statistically using path analysis. The result of hypothesis testing showed that all hypotheses were acceptable, it was concluded that organizational climate has a positive and significant direct effect on the quality of work life, job stress has a negative and significant direct effect on the quality of work life, and organizational climate has a negative and significant direct effect on job stress.